It is up to the government : political lessons learnt from the 2016 Brexit referendum - Lippert, Barbara; Brandes, Erik (2019)
Zusammenfassung: The arduous process of withdrawing the United Kingdom (UK) from the European Union (EU) began shortly after the Brexit referendum in June 2016. The “leave” vote plunged the British government into an existential crisis and led to dramatic special summits at the EU level. Looking at the British exit vote against the history of EU-related referendums reveals its peculiarities and pitfalls. The resulting mandate left the government some room for manoeuvre and initially offered plenty of options for its negotiations with Brussels. However, the government in London was not able to translate the tight “No” vote into a viable negotiating position. The EU insisted on negotiating exclusively with Her Majesty’s Government. Paradoxically, referendums in member states illustrate the European multi-level system’s dependence on states. Member states and the EU can both learn lessons by observing the British government’s handling of the exit referendum